Perkawinan Semarga Dalam Adat Mandailing Di Desa Simanosor Kabupaten Tapanuli Selatan Dalam Persfektif Hukum Adat Batak Mandailing - Wahyuni Malina Harahap; Maryati Bachtiar; Ulfia Hasanah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2018)
Marital marriage is a marriage that is prohibited in indigenous Batak Mandailing, because it is considered to be from the same lineage which means having blood relation. There are three customary marriage systems: eksogamy, endogamy and eleutherogamy. Batak mandailing community belong to the exogamy marriage system, a man is prohibited from marrying a woman of the same age or as a man. A man must marry a woman out of her family. The purpose of this thesis writing is first: to know the causes of prohibited marriage in the village simanosor south tapanuli. secondly, to find out the customary sanctions given to married offenders in the village simanosor south tapanuli district.The type of research can be classified in the type of sociological research, because in this study the authors directly conduct research on the location or place studied in order to provide a complete and clear picture of the problems studied. This research was conducted in the village Simanosor south tapanuli. Descriptive, research with the source Primary, Secondary, and tertiary, while the population and sample are marital offenders, customary leaders and villagers Simanosor. Teknik data collection of interviews, questionnaires and literature review.From the results of research there are two main things that can be concluded, first: the cause of the prohibition of marriage is due to the belief that people who have same clan. Secondly: the customary sanction given to the married offenders is offering betel in the customary assembly session, as a sacrifice requesting forgiveness for wrong, paying customary sanction to prospective in-laws, families and customary chiefs by cutting a buffalo, eaten together by Dalihan na Tolu, women who do marriage should reshuffle their clan from the mother’s side of the husband through the process of traditional ceremonies, not allowed to live village or from the community environment. This penalty is given if not able to meet the fine of one buffalo. The writer’s suggestion is, firstly: the activeness of the adat leaders to teach and guide community to understand the values of adat law and the meaning of the ban of marriage semarga. Secondly: in the application of sanctions must be more assertive aimed to give effect jeragar people are afraid to violate the provisions of customary law one of them doing marriage as a family.Keywords: mandailing customary law, marriage of sunrnsi, adat sanction.